2013
DOI: 10.1073/pnas.1311334110
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal amplification method for next-generation sequencing

Abstract: We report an approach for generating immobilized monoclonal templates for next-generation sequencing applications. Our isothermal amplification method is based on a template walking mechanism using a pair of low-melting temperature (Tm) solidsurface homopolymer primers and a low-Tm solution phase primer. The method can generate more than one billion submicrometersized colonies in a single lane of a next-generation sequencing flowchip. An alternative paired-end sequencing method using interstrand DNA photo cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 16 publications
(11 reference statements)
0
21
0
Order By: Relevance
“…The DNA libraries are labeled with barcode sample tags, such as the multiplex identifier (MID) for Roche/454 sequencing, to enable the libraries to be pooled and therefore maximize the sequence output as a multiplex amplicon sequencing step for each sequencing run. After library construction, the DNA fragments are clonally amplified by emulsion PCR with microbeads [4,6,60] or by solid-phase PCR using primers attached to a solid surface [4,61,62] in order to generate sufficient single-stranded DNA molecules and detectable signal for producing sufficiently reliable sequencing data [54]. Roche 454, Life Technologies' SOLiD, and Ion Torrent platforms use emulsion PCR, whereas Illumina's HiSeq/MiSeq platforms use solid-phase PCR [4].…”
Section: Dna and Rna Library Preparations For Second-generation Sequementioning
confidence: 99%
See 2 more Smart Citations
“…The DNA libraries are labeled with barcode sample tags, such as the multiplex identifier (MID) for Roche/454 sequencing, to enable the libraries to be pooled and therefore maximize the sequence output as a multiplex amplicon sequencing step for each sequencing run. After library construction, the DNA fragments are clonally amplified by emulsion PCR with microbeads [4,6,60] or by solid-phase PCR using primers attached to a solid surface [4,61,62] in order to generate sufficient single-stranded DNA molecules and detectable signal for producing sufficiently reliable sequencing data [54]. Roche 454, Life Technologies' SOLiD, and Ion Torrent platforms use emulsion PCR, whereas Illumina's HiSeq/MiSeq platforms use solid-phase PCR [4].…”
Section: Dna and Rna Library Preparations For Second-generation Sequementioning
confidence: 99%
“…Roche 454, Life Technologies' SOLiD, and Ion Torrent platforms use emulsion PCR, whereas Illumina's HiSeq/MiSeq platforms use solid-phase PCR [4]. More recently, isothermal PCR amplification on a solid surface of a flow cell [62] was developed for the SOLiD 5500 W series of sequencing machines.…”
Section: Dna and Rna Library Preparations For Second-generation Sequementioning
confidence: 99%
See 1 more Smart Citation
“…The assignment of barcodes to patches of a surface can be accomplished with surface polony generation methods such as bridge amplification [2], a 2primer rolling circle amplification-based method [11], template walking amplification [13], whereby unique "seed" strands are captured by the surface containing primer strands (Figure 1 A) and then locally amplified in the immediate spatial vicinity of where they landed thus generating a diverse surface of distinct patches of amplified DNA (Figure 1 B). A polony is defined as one of these locally amplified patches of DNA derived from a single seed molecule.…”
Section: Transfer Of Spatial Information To Dna Sequencesmentioning
confidence: 99%
“…Further, RPA has also been shown to be biased against sequences with high GC content (Hansen et al 2016) as the strand exchange activity of some recombinase proteins has been shown to be inhibited by GC content of 70% (Patil et al 2011). Previous studies have successfully used isothermal amplification on degraded DNA from forensic samples and formalin fixed paraffin embedded (FFPE) tissues (Tate et al 2011;Wang et al 2004), as well as modern sequencing libraries (Jasmine et al 2008;Lou et al 2013;Ma et al 2013;Oyola et al 2012). While, isothermal methods have been also used in the hybridization capture of targets from sequencing libraries made from aDNA (Haak et al 2015), their performance compared to PCR was not evaluated.…”
Section: Introductionmentioning
confidence: 99%